A review on the wear of oil drill bits (conventional and the state of the art approaches for wear reduction and quantification). (August 2018) - K. Abbas, Rafid
Abstract: Since the first use of oil drill bits to penetrate petroleum and gas wells, the wear of the teeth and bearing (for roller-cone bits) and cutters for (Polycrystalline Diamond Compact (PDC) bits) has been a major dilemma that causes money and time loss, consequently affecting the whole drilling operation. The present study reviews wear mechanisms in both bit types. The review has carried out the previous and the state of the art approaches for improving the drill bits against wear. Advantages and disadvantages of the conventional technologies for improving the manufacturing of the drill bits are explained. Conventional and emerging approaches of wear testing of drill bits are shown to expand the scope for developing the manufacturing of more reliable drill bits against the wear. We report a literature survey of the old and current methods of wear quantification in terms of drilling parameters and mechanical properties of the minerals forming the drill bits, and means of increasing the efficiency of oil and gas drill bits. Empirical wear models, as well as wear prediction techniques while drilling are discussed along with the simulation wear models using Finite Element Analysis (FEA) and the Discrete Element Method (DEM). Highlights: Conventional and emerging techniques of improving the durability of drill bits against wear were reviewed. Wear mechanism of drill bits is important to know the main reasons of their failure. Empirical models for wear quantification of drill bits and the appropriate wear testing of drill bits. Simulation approaches for bit wear determination and their application. State-of-the-art techniques to quantify the volume of wear of the oil drill bits.